Concomitant vascular and neurodegenerative pathologies double the risk of dementia - Azarpazhooh, Mahmoud Reza; Avan, Abolfazl; Cipriano, Lauren E.; Munoz, David G.; Sposato, Luciano A.; Hachinski, Vladimir (Alzheimer's & dementia, 2018)
The relative contributions of vascular and degenerative pathology to dementia are unknown. We aim to quantify the proportion of dementia explained by potentially preventable vascular lesions. We systematically searched for population-based cohorts before February 2017 reporting clinicopathological data for individuals with and without dementia. We calculated the summary proportion and absolute risk of dementia comparing subjects with and without the pathology. We identified 10 studies comprising 2856 subjects. Vascular-type pathology and mixed pathology are respectively two and three times more likely in demented patients. The summary proportion of dementia is 77%–86% in subjects with mixed degenerative and vascular pathology and 45% in subjects with pure Alzheimer-type pathology. Patients with mixed pathologies have nearly twice the incremental risk of dementia compared with patients with only Alzheimer-type lesions. Consequently, many cases of dementia could be prevented or delayed by targeting the vascular component. •Vascular lesions were the most frequent types of brain lesions (44%) in the elderly.•Vascular-type pathology is two-times more likely in demented vs. nondemented subjects.•Mixed pathology doubles the risk of dementia compared with only degenerative lesions.•Mixed pathology is three-times more likely in demented vs. nondemented subjects.•Many cases of dementia could be prevented or delayed by targeting vascular component.